THE USAGE OF ADJECTIVE AND ADVERB IN ENGLISH AND THEIR DIFFERENCES - Toshtemirova Shaxzoda Sanjar qizi (PEDAGOGS, 2024)
Abstract: This article provides a clear explanation of adjectives and adverbs, which are difficult for most language learners to understand and distinguish from each other. How to distinguish between adjectives and adverbs in sentences is also explained on the basis of examples